Transforming Care: Social Rehabilitation Services for Children with Disabilities in Ukraine - Slozanska, Anna; Petrochko, Zhanna; Horishna, Nadiya; Stoliaryk, Olha; Krynytska, Iryna (Socialinė teorija, empirija, politika ir praktika, 2025)
The article examines the provision of social rehabilitation services to children with disabilities and their parents within Ukrainian territorial communities. The study aims to identify priorities and challenges in delivering these services and to propose measures for enhancing their quality. A qualitative research methodology was employed, utilizing expert interviews with 13 specialists from the Lviv, Ternopil, and Cherkasy regions, including both administrators and practitioners who work directly with children with disabilities and their families. The findings highlight that early intervention and day care services as essential priorities, alongside supported living, transportation, assistance during inclusive education, and social orientation programmes. The key challenges include insufficient interdisciplinary collaboration, inadequate information exchange about available services, limited access for children with disabilities, low professional competence among specialists, and issues related to material, technical, and financial support. Recommendations for improving the service quality encompass systematic monitoring of rehabilitation processes, prioritizing professional support within children’s immediate environments, adopting an integrated service provision approach, ensuring children’s participation in decision-making, enhancing competencies of parents and professionals, strengthening social partnerships, promoting fundraising initiatives, conducting awareness campaigns, and fostering international cooperation. This study contributes to the theory and practice of local social work by providing actionable insights to improve social rehabilitation services for children with disabilities in Ukraine, thereby promoting inclusivity and social cohesion.